Pioneering Use of Ionic Liquid‐Based Aqueous Biphasic Systems as Membrane‐Free Batteries. Issue 10 (8th August 2018) - Navalpotro, Paula; Neves, Catarina M. S. S.; Palma, Jesus; Freire, Mara G.; Coutinho, João A. P.; Marcilla, Rebeca
Abstract: Aqueous biphasic systems (ABS) formed by water, ionic liquids (ILs), and salts, in which the two phases are water rich, are demonstrated here to act as potential membrane‐free batteries. This concept is feasible due to the selective enrichment of redox organic molecules in each aqueous phase of ABS, which spontaneously form two liquid‐phases above given concentrations of salt and IL. Therefore, the required separation of electrolytes in the battery is not driven by an expensive membrane that hampers mass transfer, but instead, by the intrinsic immiscibility of the two liquid phases. Moreover, the crosscontamination typically occurring through the ineffective membranes is determined by the partition coefficients of the active molecules between the two phases. The phase diagrams of a series of IL‐based ABS are characterized, the partition coefficients of several redox organic molecules are determined, and the electrochemistry of these redox‐active immiscible phases is evaluated, allowing appraisal of the battery performance. Several redox ABS that may be used in total aqueous membrane‐free batteries with theoretical battery voltages as high as 1.6 V are identified. The viability of a membrane‐free battery composed of an IL‐based ABS containing methyl viologen and 2, 2, 6, 6‐tetramethyl‐1‐piperidinyloxy as active species is demonstrated. Abstract : The feasibility of ionic liquid‐based aqueous biphasic systems (IL‐ABS), as immiscible aqueous‐aqueous redox electrolytes for an innovative electrochemical energy storage device, namely a membrane‐free battery, is demonstrated. The IL‐ABS are advantageous to control the crossmigration of the species in the innovative membrane‐free batteries field. The membrane‐free battery is an up‐and‐coming application for the ABS platform.